Sustainability and Resiliency Dimensions of Go Public Companies: The Role of Audit Report Lag and Earning Volatility in Impacting The Earning Quality - Oktapriana, Chita; Reyes, Mila Austria (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
The information needs of stakeholders in today's business world do not only depend on financial statements alone. There is a global push for sustainability disclosures and the durability of companies can be shown through sustainability reports. One of the important elements that can positively encourage corporate sustainability can be measured through the quality dimension of earnings.The length of time that separates the management cutoff from the audit report issuance response might have an impact on the financial statements' quality, particularly in regards to the reported earning quality.For companies that have gone public, higher disclosure quality will provide a positive signal to investors that the operations carried out are able to show resilience that leads to sustainability in the future. Earning quality in this study will be measured through the level of earning smoothness, earning surprice, closeness to cash and accrual quality.  Additionally, the impact on earning quality will be greater if the organization has a larger earning volatility ratio. The purpose of this study is to investigate how the company's earning quality is impacted by earning volatility and audit report latency. With a total of 170 data, this study employs a linear regression test via the SPSS 26 test tool. The hypothesis test results show that the earning volatility ratio and earning quality have a significant relationship. Earning quality is significantly impacted by both earning volatility and audit report lag at the same time.